LYAPUNOV EXPONENTIALLY STABILITY FOR SOME MODELS NONLINEAR PDEs - Raed A. Hameed,Wafaa M. Taha, Sabaa Mazin Modhher, A R Seadawy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to analyzing exponential stability of non-linear partial differential equation using Lyapunov second method. We consider different models from heat and wave non-linear equations in addition to 2×2 hyperbolic system with balance laws. We show the effectiveness of the proposed methodology using some examples of different types of nonlinear PDEs.